Kadın futbolcularda sekiz hafta boyunca uygulanan farklı kontrast kuvvet antrenman metotlarının performans çıktısına etkisi - Çıkıkcı, Alper (My University, 2023)
Kadın Futbolcularda Sekiz Hafta Boyunca Uygulanan Farklı Kontrast Kuvvet Antrenman Metotlarının Performans Çıktısına Etkisi Öğrencinin Adı: Alper ÇIKIKCI Amaç: Kadın futbolcuların 8 haftalık süreç içerisinde futbol antrenmanları ile birlikte uygulanan iki farklı kontrast antrenman modelinin, atletik performans çıktılarına etkisinin araştırılmasıdır. Gereç ve Yöntem: Türkiye Futbol Federasyonu Kadınlar Süper liginde oynayan, 29 kadın futbolcu, iki ayrı gruba ayrılarak A ve B antrenman grubunu oluşturmuşlardır. Her iki antrenman grubu da hem agonist hem de antagonist kontrast antrenmanlarını haftada 2 defa ve 4 hafta süresince olacak şekilde uygulamışlardır. İki grupta antrenmanlara başlamadan önce, Maksimal sprint sürati, drop jump, counter movement jump, squat jump, pro agility,10 ve 30 m sprint testlerini gerçekleştirmişlerdir. İki grupta dördüncü haftanın sonunda ara testlerini olup agonist ve antagoist olan modelleri değişmişler ve 4 hafta sonunda tekrar bu testler gerçekleştirilmiştir. Bulgular: Antagonist antrenman, A grubunda maksimal sprint sürati (30 m), drop jump, squat jump, counter movement ölçümlerinde, B grubunda pozitif ivmelenme (10 m), maksimal sprint sürati ölçümlerinde anlamlı fark bulunmaktadır (p<0,05). Agonist antrenman, A grubunda yön değiştirme, drop jump, squat jump ölçümlerinde, B grubunda yön değiştirme, squat jump, counter movement jump ölçümlerinde anlamlı fark bulunmaktadır (p<0,05). Sonuç: Antagonist antrenman A grubunda maksimal sprint sürati, drop jump, squat jump, counter movement jump değerlerinde, B grubunda pozitif ivmelenme (10 m) ve maksimal sprint sürati değerlerinde gelişim sağlamıştır. Agonist antrenman, A grubunda yön değiştirme, drop jump, squat jump değerlerinde, B grubunda yön değiştirme, squat jump, counter movement jump değerlerinde gelişim sağlamıştır.

The Effect of Different Contrast Strength Training Methods Applied of 8 Weeks on the Performance of Female Footballers Student Name, Surname: Alper ÇIKIKCI Objective: To investigate the effect of two different contrast training models applied in combination with soccer training on athletic performance outcomes of female soccer players over an 8-week period. Materials and Methods: Twenty-nine female soccer players, playing in the Women's Super League of the Turkish Football Federation, were divided into two groups A, and training group B. Both training groups practiced both agonist and antagonist contrast training twice a week for 4 weeks. Maximal sprint speed, drop jump, counter movement jump, squat jump, squat jump, pro agility, 10 and 30 m sprint tests were performed in both groups before starting the training. At the end of the fourth week, the two groups performed the interim tests at the end of the fourth week and the agonist and antagonist models were changed and these tests were performed again at the end of 4 weeks. Results: There is a significant difference (p<0.05) between the first and second test in the measurements of maximal sprint speed (30 m), drop jump, squat jump, counter movement in group A and positive acceleration (10 m), maximal sprint speed in group B. There is a significant difference between the 1st and 2nd test in change of direction, drop jump, squat jump measurements in group A and change of direction, squat jump, counter movement jump measurements in group B (p<0,05). Conclusion: Antagonist training improved maximal sprint speed, drop jump, squat jump, squat jump, counter movement jump in group A, and positive acceleration (10 m) and maximal sprint speed in group B. Agonist training improved change of direction, drop jump, squat jump values in group A and change of direction, squat jump, counter movement jump values in group B.
The effect of different contrast strength training methods applied of 8 weeks on the performance of female footballers
Keywords: Beden eğitimi ve antrenman; Contrast Training; Futbol; Kadın Futbol; Kadın futbolcuların; Kontrast Antrenman Football; Kuvvet Antrenmanı; Physical education and training; Strength Training; Women athletes; Women Football